2004
DOI: 10.1542/peds.113.3.e238
|View full text |Cite
|
Sign up to set email alerts
|

Otitis Media and Speech and Language: A Meta-analysis of Prospective Studies

Abstract: ABSTRACT. Objective. Considerable controversy surrounds whether a history of otitis media with effusion (OME) in early childhood causes later speech and language problems. We conducted a meta-analysis of prospective studies to determine: 1) whether a history of OME in early childhood is related to receptive language, expressive language, vocabulary, syntax, or speech development in children 1 to 5 years old and 2) whether hearing loss caused by otitis media in early childhood is related to children's receptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
153
1
16

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(177 citation statements)
references
References 49 publications
2
153
1
16
Order By: Relevance
“…Moreover, Turcanu et al (2009) The presence of an MEE is not necessarily indicative of the presence of a CHL-implications for long-term hearing impairments due to chronic CHL Although most children experience multiple bouts of OME during early childhood, it is less clear whether OME typically presents with a corresponding CHL. This distinction is critical, as the mere presence of OME alone without associated CHL would not be expected to result in long-term hearing deficits (Roberts et al 2004). However, OME that has been clinically documented to coincide with a corresponding CHL has been shown to result in altered auditory physiology and auditory behavior in a majority of cases (for review, see Whitton and Polley 2011); children with these conditions have a high likelihood of developing persistent hearing deficits.…”
Section: Umbo Velocity Changes Resulting From Mees Are Volume and Frementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Turcanu et al (2009) The presence of an MEE is not necessarily indicative of the presence of a CHL-implications for long-term hearing impairments due to chronic CHL Although most children experience multiple bouts of OME during early childhood, it is less clear whether OME typically presents with a corresponding CHL. This distinction is critical, as the mere presence of OME alone without associated CHL would not be expected to result in long-term hearing deficits (Roberts et al 2004). However, OME that has been clinically documented to coincide with a corresponding CHL has been shown to result in altered auditory physiology and auditory behavior in a majority of cases (for review, see Whitton and Polley 2011); children with these conditions have a high likelihood of developing persistent hearing deficits.…”
Section: Umbo Velocity Changes Resulting From Mees Are Volume and Frementioning
confidence: 99%
“…On the other hand, clinically, OME might be present (as indicated by tympanometry and visual inspection), but the CHL could be negligible. Thus, children with chronic OME should ideally receive hearing tests to determine the presence and magnitude of an MEEinduced CHL (Roberts et al 2004). …”
Section: Umbo Velocity Changes Resulting From Mees Are Volume and Frementioning
confidence: 99%
“…1,3,4 Despite the high prevalence of OME, its long-term impact on child developmental outcomes, such as speech, language, intelligence, and hearing remain disputed. 5 A recent systematic review of the natural history of OME found mixed evidence regarding the impact of OME in early childhood on later developmental outcomes. 2 Lacking clear evidence that OME influences children' s development, clinicians struggle with decision-making for this common condition.…”
mentioning
confidence: 99%
“…Since otitis is more frequent during the first year of life, studies have demonstrated that its relapse may cause, to a larger or shorter extent, speech development delay or problems. 48 Thus, with regard to speech, pacifiers are, at the same time, used to consolidate sucking and coordinate suckingswallowing-breathing and considered a negative habit.…”
Section: Speech Therapymentioning
confidence: 99%